FILSAFAT PEMIDANAAN TERHADAP PENYALAH GUNA NARKOTIKA BAGI DIRI SENDIRI DAlAM PERSPEKTIF HUKUM POSITIF DAN HUKUM PIDANA ISLAM - Kurniasih Bahagiati (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2020)
This article aims to discuss the philosophy of punishment for the misuse of narcotics for oneself from the perspective of positive criminal law and Islamic criminal law. The approach used in this study is normative juridical and uses the statutory approach, philosophical approach, comparative approach, and conceptual approach. Data sources used in this study are secondary data consisting of official documents, books, and research results. The results of this study are according to positive criminal law, imprisonment, and rehabilitation are in accordance with the philosophy of criminal law with the concept of a double-track system. Still, in practice, the Judges more often decide cases of narcotics abuse for themselves with imprisonment. In the perspective of Islamic criminal law, abusers of narcotics for themselves are also seen as victims of crimes committed by themselves, so that the proper punishment against them is the sanction of rehabilitation measures. Imposing sanctions in the form of rehabilitation measures are in accordance with the philosophy of punishment in Islamic criminal law because it considers the principles of maqoshid shari'ah